Pathfinders : extraordinary stories of people like you on the quest for financial independence--and how to join them - Collins, J. L. (Blogger) (Harriman House, 2023)
From "The Godfather of FI", a follow-up to his international bestselling finance sensation The Simple Path to Wealth. Pathfinders brings together scores of amazing and insightful real-life stories from real people on a quest to find financial independence--providing practical encouragement and inspiration for anyone who wants to join them.